Analysis of the Suitability of Media and Learning Resources Used by Teachers Learning Needs of High School Physics in the 21st Century The Material of Light and Sound Waves - Dewi, Utari Prisma; Desnita, Desnita; Usmeldi, Usmeldi; Fauzi, Ahmad (Jurnal Penelitian Pembelajaran Fisika, 2024)
This research aims to analyze the media needs and learning resources used by high school physics teachers regarding light and sound waves. The method used in this research is descriptive research with a quantitative approach. The instrument used in this research was a questionnaire in the form of a Google Form link which was given to class XI students from 6 schools. The results of the analysis show that the learning media that is most widely used in 6 schools regarding sound and light waves is other media in the form of blackboards with an average percentage of 30%. Meanwhile, the most widely used learning resource is printed books with a percentage of 40%. Based on the results of the analysis, it can be concluded that IT-based learning media in schools is still not optimal. So that students become intelligent, critical, creative and hardworking individuals, who are no less competitive than other competitors, the solution provided so that students' learning resources are in line with technological developments is to use e-modules.Keywords: learning media, learning resources, light and sound waves.